EFEKTIVITAS MEDIA ARABIC TOWER UNTUK MENINGKATKAN MAHARAH KALAM SISWA SMP MUHAMMADIYAH 1 SIDOARJO - Sa'diyah, Afifah Dzati; Hikmah, Khizanatul (Jurnal Dedikasi Pendidikan, 2024)
Language is a structured communication system with elements such as words, word sequences, and sentences. Arabic itself has a central role in the educational structure in Indonesia, especially as an integral part of religious education. This research aims to evaluate the effect of using Arabic Tower media on increasing the maharah kalam of grade 8 students at SMP Muhammadiyah 1 Sidoarjo. The research method used was an experiment with a Pretest Posttest Control Group design. The population used was grade 8 with 34 students as samples. Data was collected through observation, interviews and tests, then analyzed using SPSS version 19 software. The conclusion of this research is that there has been an increase in Maharah Kalam. Through hypothesis results with a Sig value. (2-Tailed) 0.000, in other words, Arabic Tower media is effective in increasing Maharah Kalam in class 8 students of SMP Muhammadiyah 1 Sidoarjo. The strengths and weaknesses of Arabic Tower media are also identified, providing insight into the potential and limitations of its use in Arabic language learning contexts.